Genome sequence and comparative analysis of reindeer (Rangifer tarandus) in northern Eurasia - Weldenegodguad, Melak; Pokharel, Kisun; Ming, Yao; Honkatukia, Mervi; Peippo, Jaana; Reilas, Tiina; Røed, Knut H.; Kantanen, Juha
Reindeer are semi-domesticated ruminants that have adapted to the challenging northern Eurasian environment characterized by long winters and marked annual fluctuations in daylight. We explored the genetic makeup behind their unique characteristics by de novo sequencing the genome of a male reindeer and conducted gene family analyses with nine other mammalian species. We performed a population genomics study of 23 additional reindeer representing both domestic and wild populations and several ecotypes from various geographic locations. We assembled 2.66 Gb (N50 scaffold of 5 Mb) of the estimated 2.92 Gb reindeer genome, comprising 27,332 genes. The results from the demographic history analysis suggested marked changes in the effective population size of reindeer during the Pleistocene period. We detected 160 reindeer-specific and expanded genes, of which zinc finger proteins (n = 42) and olfactory receptors (n = 13) were the most abundant. Comparative genome analyses revealed several genes that may have promoted the adaptation of reindeer, such as those involved in recombination and speciation (PRDM9), vitamin D metabolism (TRPV5, TRPV6), retinal development (PRDM1, OPN4B), circadian rhythm (GRIA1), immunity (CXCR1, CXCR2, CXCR4, IFNW1), tolerance to cold-triggered pain (SCN11A) and antler development (SILT2). The majority of these characteristic reindeer genes have been reported for the first time here. Moreover, our population genomics analysis suggested at least two independent reindeer domestication events with genetic lineages originating from different refugial regions after the Last Glacial Maximum. Taken together, our study has provided new insights into the domestication, evolution and adaptation of reindeer and has promoted novel genomic research of reindeer. 2020